An Organic Molecule with Asymmetric Structure Exhibiting Aggregation‐Induced Emission, Delayed Fluorescence, and Mechanoluminescence1. (2nd December 2014) - Xu, Shidang; Liu, Tingting; Mu, Yingxiao; Wang, Yi‐Fan; Chi, Zhenguo; Lo, Chang‐Cheng; Liu, Siwei; Zhang, Yi; Lien, Alan; Xu, Jiarui
Abstract Compounds displaying delayed fluorescence (DF), from severe concentration quenching, have limited applications as nondoped organic light‐emitting diodes and material sciences. As a nondoped fluorescent emitter, aggregation‐induced emission (AIE) materials show high emission efficiency in their aggregated states. Reported herein is an AIE‐active, DF compound in which the molecular interaction is modulated, thereby promoting triplet harvesting in the solid state with a high photoluminescence quantum yield of 93.3 %, which is the highest quantum yield, to the best of our knowledge, for long‐lifetime emitters. Simultaneously, the compound with asymmetric molecular structure exhibited strong mechanoluminescence (ML) without pretreatment in the solid state, thus exploiting a design and synthetic strategy to integrate the features of DF, AIE, and ML into one compound.